A DIRECT MEASUREMENT OF THE SURFACE MAGNETIZATION OF A FERROMAGNETIC METALLIC-GLASS - Ivison, P; Cowlam, N; Gibbs, M; Penfold, J; Shackleton, C (1989)
The first-ever measurements of the surface magnetisation of a metallic glass specimen using neutron reflectivity are presented. These have been made on commercial METGLAS 2605S2 metallic glass ribbon using the CRISP neutron reflectometer on the ISIS Spallation Neutron Source at the SERC Rutherford Appleton Laboratory. The reflectivity data were analysed by fitting a model to the data which has enabled an estimate of the magnetisation profile near to the ribbon surface to be made. Long-range variations (with a length scale approximately 80 AA) at the surface of the ribbon have been observed, in which the apparent magnetic moment value at the surface is approximately half that in the bulk. These results can be interpreted in terms of noncollinear moment arrangements which follow the irregularities at the surface.